Present State and Prospects of Ice Sheet and Glacier Modelling - Blatter, Heinz; Greve, Ralf; Abe-Ouchi, Ayako (2018)
Since the late 1970s, numerical modelling has become established as an important technique for the understanding of ice sheet and glacier dynamics, and several models have been developed over the years. Ice sheet models are particularly relevant for predicting the possible response of ice sheets to climate change. Recent observations suggest that ice dynamics could play a crucial role for the contribution of ice sheets to future sea level rise under global warming conditions, and the need for further research into the matter was explicitly stated in the Fourth Assessment Report (AR4) of the United Nations Intergovernmental Panel on Climate Change (IPCC). In this paper, we review the state of the art and current problems of ice sheet and glacier modelling. An outline of the underlying theory is given, and crucial processes (basal sliding, calving, interaction with the solid Earth) are discussed. We summarise recent progress in the development of ice sheet and glacier system models and their coupling to climate models, and point out directions for future work